2017
DOI: 10.1038/onc.2017.248
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma stem cells exploit the αvβ8 integrin-TGFβ1 signaling axis to drive tumor initiation and progression

Abstract: Glioblastoma (GBM) is a primary brain cancer that contains populations of stem-like cancer cells (GSCs) that home to specialized perivascular niches. GSC interactions with their niche influence self-renewal, differentiation and drug resistance, although the pathways underlying these events remain largely unknown. Here, we report that the integrin αvβ8 and its latent transforming growth factor β1 (TGFβ1) protein ligand have central roles in promoting niche co-option and GBM initiation. αvβ8 integrin is highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 68 publications
5
38
0
Order By: Relevance
“…We first demonstrated in GB patient primocultures that b8 is strongly overexpressed at the GIC surface. We also highlighted a stronger b8 expression in GIC compared with their differentiated counterparts, as already suggested in GB cells (9,17), but also in colorectal cancer cells (28). In addition, we analyzed TCGA database and found that b8 expression in GB samples is correlated positively with the expression of numerous stem markers and negatively with neural differentiation markers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We first demonstrated in GB patient primocultures that b8 is strongly overexpressed at the GIC surface. We also highlighted a stronger b8 expression in GIC compared with their differentiated counterparts, as already suggested in GB cells (9,17), but also in colorectal cancer cells (28). In addition, we analyzed TCGA database and found that b8 expression in GB samples is correlated positively with the expression of numerous stem markers and negatively with neural differentiation markers.…”
Section: Discussionsupporting
confidence: 75%
“…Although few studies were conducted in glioma, b8 appears to have a proinvasive role in GB cells (15), whereas it could negatively regulate angiogenesis in transformed human astrocytes (16). In addition, it was recently shown that b8 HIGH -GB cells display several stem characteristics (17). Nevertheless, the effects of b8 targeting on GIC stemness, viability, migration, radioresistance, and tumorigenicity have never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In GBM, targeting of the pro-angiogenic avb3 and b5 integrins with cilengitide failed to improve patient outcome in a phase III clinical trial (Stupp et al, 2014). However, other integrin receptors, such as the laminin-binding a6 and a7 integrins or the RGD receptor avb8 integrin, are regarded as putative therapeutic targets, as their expression on GSCs promotes selfrenewal, proliferation, and tumor formation (Guerrero et al, 2017;Haas et al, 2017;Lathia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The integrin αvβ8-TGF-β1 axis contributes to the regulation of angiogenesis and invasiveness of glioblastoma [40]. Altering integrin αvβ8 levels had an obvious effect on the angiogenic and invasive growth properties of glioblastoma, in part, reflected by a diminished activation of latent TGF-β [43]. However, the role of integrin αvβ8 in invasion and migration of epithelial neoplasms, especially colon cancer has not been well elucidated.…”
Section: Discussionmentioning
confidence: 99%